Analisis peranan sektor pertanian dalam pertumbuhan ekonomi dan distribusi pendapatan di Provinsi Papua Barat - Merry Merry; Bambang Nugroho; Ihwan Tjolli (Cassowary, 2020)
This study aims to analyze the contribution of agricultural sector to Gross Domestic Product (GDP), employment, and economic growth, analyze/calculate the amount of income inequality that happened, and analyze/identify the role of the agricultural sector towards the income distribution in districts/cities and economic growth in West Papua Province. This research was conducted in the province of West Papua by collecting data at BPS-Statistics Indonesia, Regional Planning Agency, Department of Agriculture of West Papua Province and other relevant technical agencies. The data required consist of GDP by sector of each district/city in West Papua Province by constant price, the total population by district / city, the percentage of the population aged over 15 years who worked under major employment field, and various other secondary data and some from the results of previous studies. The period of analysis in this study is 2000 to 2012. Data processing will be done with the help of software such as Microsoft Excel 2010, and SPSS. The analysis showed that the agricultural sector has a considerable contribution in the regional economy of West Papua province which accounted for an average of 37,96 percent per year of the total GDP. The result of analysis shows that income inequality has occurred in districts/cities in West Papua Province, one of which is caused by the agricultural sector. There is an increasing in the inequality index when the agricultural GDP is omitted. Inequality index with agricultural GDP is included is in the range of 0,20 and when agricultural GDP is eliminated the inequality index increases to about 0,40. In other words, the agricultural sector has a significant role in reducing income inequality in districts/cities and is also able to increase the economic growth of West Papua Province. The result of a positive correlation (0.928) is present between the share of agricultural GDP and employment, the decreasing of the share of agricultural GDP was accompanied by the decreasing of agricultural employment. On the other hand, the relationship between the share of agricultural GDP and economic growth rate is negative (-0.659) or the opposite direction relationship.